Is the male-to-female transgender travel experience similar to cisgender female travel experience and in what ways are they different - Lakes, Suresh Oliver (Nanyang Technological University, 2023)
This research seeks to understand in what ways the travel experiences of transgender women are different from those of cisgender women. Though much literature is available, they focus only on differences in airport spaces. The purpose of this study is to delve deeply into the lived experience of transgender women travellers by analysing social media content (YouTube) to discover the similarities and differences between the female transgender traveller and the cisgender traveller. The findings suggest that, like cisgender women, transgender women also fear sexual violence while travelling. Transgender women also love to engage in cultural activities such as cooking and homestay, similar to their cisgender counterparts. Unlike cisgender women, transgender women are more culturally sensitive, and try to blend in through the use of cultural artefacts such as clothing, and by attempting to learn and speak the language. However, limits to blending in exists based on the extent of ‘passability’ and success. The absence of attention in their home country means that transgender women seek more attention from countries that display tolerance. In terms of their perception of poverty, they, like many other individuals from wealthy nations, believe that poverty is associated with nobility and that poor people are actually happy. Overall, the research indicated that while transgender women travellers are similar to cisgender women in many ways, there are some differences.